Genetic Polymorphism of paraoxonase 3 gène Ala99Ala in Adja and Mahi ethnic groups in Benin - SEGBO, JULIEN A. GAÉTAN; MISSIHOUN, ANTOINE ABEL HOUMÈNOU; AGBANGLA, CLÉMENT (My University, 2017)
Introduction: The paraoxonase has anti-atherogenic activity which may be altered by the coding gene polymorphisms. The purpose of this study was to assess the genotypic distribution and allelic frequencies in paraoxonase 3 gene Ala99Ala polymorphism in Beninese Adja and Mahi ethnic groups. Materials and methods: The paraoxonase 3 gene Ala99Ala polymorphism of 144 subjects of Beninese Adja and Mahi ethnic groups was studied using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism technique and compared with that in Beninese Abomey-Calavi population and others word populations. Results: The alleles A and G frequencies were 67.0 percent and 33.0 percent respectively of Adja ethnic group; and 66.0 percent and 34.0 percent respectively of Mahi ethnic group. There were no significant ethnic differences for these allelic frequencies between these two ethnic groups. Conclusion: The genotypic distribution and allelic frequencies of paraoxonase 3 gene Ala99Ala polymorphism in Beninese Adja and Mahi ethnic groups were significantly different from those in Beninese Abomey-Calavi population and in others word populations respectively.
Keywords: Single Nucleotide Polymorphism; gene; distribution; population